Evaluasi Kinerja Karyawan Kontrak Menggunalan Metode Fuzzy Tsukamoto - Kartika Sari; Rosma Siregar (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Contract employees are employees who work in contact with a certain time agreement. However, there are times when contact employees with good performance will change their status to permanent employees. To determine whether an employee is a permanent employee, an evaluation of whether the employee's performance is worthy of being appointed as a permanent employee is required. However, to carry out this evaluation, a variable is needed to make an assessment. In the performance evaluation it is not easy to determine the value of each variable. To assist an HRD in determining the appointment of a contact employee to become a permanent employee, a decision support system is needed to facilitate HRD work. The decision support system is made using the Tsukamoto fuzzy logic method because the Tsukamoto fuzzy has a tolerance for value data. The result of the research is that the employee can be appointed as a permanent employee with a value of 93.4. The purpose of this decision support system is to determine whether or not contract employees are eligible to become permanent employees based on alternative disciplines, ways of working and behavior.